2017
DOI: 10.1016/j.aller.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of airway and systemic inflammation in obese asthmatic paediatric patients

Abstract: This is the first study to investigate levels of hs-CRP, NGAL, OPN, MMP-9, and 25(OH)-vitamin D in obese asthmatic children. Larger studies with sputum and BAL examinations are required to determine the potential of biomarkers for identifying inflammation in obese asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…16 In a study conducted by Akelma et al, 24 serum osteopontin levels were found to be higher in children with asthma than in controls and higher in those with allergic rhinitis than those without. In another study conducted by Nacaroglu et al, 25 no difference was found between children with asthma and the control group in terms of osteopontin levels. According to a recently published meta-analysis including these two studies, osteopontin expression in participants with asthma was found to be higher than that in the healthy controls.…”
Section: Discussionmentioning
confidence: 81%
“…16 In a study conducted by Akelma et al, 24 serum osteopontin levels were found to be higher in children with asthma than in controls and higher in those with allergic rhinitis than those without. In another study conducted by Nacaroglu et al, 25 no difference was found between children with asthma and the control group in terms of osteopontin levels. According to a recently published meta-analysis including these two studies, osteopontin expression in participants with asthma was found to be higher than that in the healthy controls.…”
Section: Discussionmentioning
confidence: 81%
“…Obesity is associated with increased incidence of asthma [ 46 ] and poor symptom control [ 47 ]. The mechanisms behind the effect of obesity on asthma are not fully understood, but proposed processes include lung mechanics such as decreased lung volume [ 48 ] and increased systemic inflammation due to pro-inflammatory cytokines released from adipose tissue [ 49 ]. Obese individuals are less responsive to ICS than non-obese individuals [ 50 , 51 ], and this is possibly due to modifications in the glucocorticoid response pathways in obese asthmatics [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is seen in pro-inflammatory adipokines and proteins released from the adipose tissue in obese individuals. It is thought that these adipokines contribute to asthma and the hypersensitivity of the airways by inducing airway inflammation or increasing existing inflammation [15].…”
Section: Active Participation Of Mediators Of Adipose Tissue – Systemmentioning
confidence: 99%
“…For example, it has been shown that markers of metabolic inflammation, mainly in visceral adipose tissue, are significantly higher in obese patients with late-onset asthma compared with control subjects. While there is clear evidence of increased systemic inflammation in adults who are asthmatic-obese, there is conflicting evidence regarding systemic inflammation in children who are asthmatic-obese [1, 15].…”
Section: Active Participation Of Mediators Of Adipose Tissue – Systemmentioning
confidence: 99%